2015
DOI: 10.1007/s11011-015-9732-7
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A1, B levels, and their ratio and the risk of a first stroke: a meta-analysis and case–control study

Abstract: The associations of levels of apolipoprotein A1 (ApoA1) and apolipoprotein B and ApoB/A1 ratio and risk of a first stroke have not been reliably documented. We performed a meta-analysis to summarize the relationships and confirmed them in a case-control study. We identified relevant publications in PubMed and Embase databases up to June 1, 2015. A Dersimonian-Laird random effects model was used to compute summary relative risks (RRs) and 95 % confidence intervals (CIs). A case-control study was conducted in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 29 publications
5
32
0
1
Order By: Relevance
“…Several studies have indicated an correlation of the ApoB/ApoA1 ratio and the risk of stroke (Dong et al, ; Kostapanos et al, ), intracranial and extracranial carotid stenosis (Park et al, , ). But no prior study has demonstrated a correlation between the ApoB/ApoA1 ratio and RN in patients after radiotherapy for NPC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have indicated an correlation of the ApoB/ApoA1 ratio and the risk of stroke (Dong et al, ; Kostapanos et al, ), intracranial and extracranial carotid stenosis (Park et al, , ). But no prior study has demonstrated a correlation between the ApoB/ApoA1 ratio and RN in patients after radiotherapy for NPC.…”
Section: Discussionmentioning
confidence: 99%
“…The ApoA1 level refers to a marker of antioxidant and anti‐inflammatory properties (Walldius & Jungner, ). While, the ApoB is a marker of oxidative and atherogenic properties (Dong et al, ). The elevated ApoB/ApoA1 ratio mirrors the unbalance of proinflammation and anti‐inflammation, which might enhance the RN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymerase chain reaction (PCR) was used to amplify the fragment of 433 bp at the 5' end of the apoAI gene. To amplify the 5' end of the apoAI gene containing the polymorphic MspI sites, the following primer sequences were used: forward primer 5'-AGGGACAGAGCTGATCCTTGAACTCTTAAG-3, and reverse primer was 5'-TTAGGGGACACCTACCCGTCAGGAAGAGCA-3' (5,12). PCR was carried out in a 25 µl final volume containing 10 pmol of each primer, 50 ng genomic DNA, 2.5 µl of 10 × reaction buffer, 2 mM MgCl 2 , 0.1 mM dNTP, and 1 unit of Taq DNA polymerase.…”
Section: Dna Isolation and Genotypingmentioning
confidence: 99%
“…ApoB-and apoAI-containing lipoproteins are potentially atherogenic and anti-atherogenic, respectively. The ratio between apoB/apoAI could show a balance between atherogenic and anti-atherogenic lipoproteins (11,12). ApoAI, the main apolipoprotein of HDL, is a candidate gene for dyslipidemia pathophysiology.…”
Section: Introductionmentioning
confidence: 99%